Efektifitas dan Kepuasan Mahasiswa terhadap Model Pembelajaran Blended Learning Bahasa Mandarin di Masa Pandemi - Nanda Lailatul Qadriani; Sri Hartati (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2023)
The transition of learning from offline to online during the Covid-19 pandemic initially presented many challenges. The limited ability of lecturers to master educational technology and the lack of experience in teaching online make lecturers tend to apply more virtual face-to-face methods as an alternative to learning in the classroom. However, implementing the virtual face-to-face method raises new problems, including students' declining psychological condition, health, and learning motivation. It becomes an in-depth evaluation for lecturers to design online learning that is more varied, interactive, and effective. Blended learning in this research is a blending of four online learning media: 1) virtual face-to-face with Zoom, 2) learning with Youtube videos, 3) learning with Edpuzzle, and 4) independent learning with assignments in LMS. This research aims to determine the effectiveness of blended learning and student satisfaction by combining four media in the online classroom. This research is  an action research consisting of 3 cycles and carried out for two semesters for students of the Chinese Language and Culture Study Program, University of Al Azhar Indonesia, Class of 2019 and 2020. The results of this study include student responses about the learning media they like the most and most effective, the strengths and weaknesses of each media, and the level of effectiveness and student learning satisfaction with implementing blended learning.